Answer:
1. 2(9x+3)
2. 3(6x+2)
3. 6(3x+1)
Explanation:
Okay so in the first one there is a 2 outside of the parentheses which means we will multiply whatever is inside of the parentheses by 2.
9x*2=18x
3*2=6
18x+6=2(9x+6)
Okay so in the second one there is a 3 outside of the parentheses which means we will multiply whatever is onside of the parentheses by 3.
6x*3=18x
2*3=6
18x+6=3(6x+2)
Okay so in the third one there is a 6 outside of the parentheses which means we will multiply whatever is inside of the parentheses by 6.
3x*6=18x
1*6=6
18x+6=6(3x=1)